2022
DOI: 10.21203/rs.3.rs-1323664/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding Sexual Reproductive Health from the perspective of Older Adolescents in Northern Thailand: A Phenomenological study

Abstract: Background: Worldwide, Sexual Reproductive Health (SRH) issues comprise a third of health problems for women aged 15-44. SRH education equips people with knowledge of concepts around sexuality and reproduction, and the attitudes and skills help to make informed decisions to prevent sexual and reproductive ill-health problems, including unplanned pregnancy and HIV/AIDS, and other sexually transmitted infections (STIs). The aim of this study is to explore the experiences of older adolescents relating to SRH, exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…nausea, headache and migraine, weight gain, breast tenderness or mood swings) were barriers to use and this supports findings from previous studies. 26,45,46 This study also revealed that the reasons for discontinuation or non-use of family planning were lack of sex education and contraceptive methods as well as fear and concern about contraception. Meanwhile, other studies illustrated a similar barrier to contraceptive use in terms of fear of side effects by users.…”
Section: The Power Of Inclusive Sex Education and Contraceptionmentioning
confidence: 74%
See 3 more Smart Citations
“…nausea, headache and migraine, weight gain, breast tenderness or mood swings) were barriers to use and this supports findings from previous studies. 26,45,46 This study also revealed that the reasons for discontinuation or non-use of family planning were lack of sex education and contraceptive methods as well as fear and concern about contraception. Meanwhile, other studies illustrated a similar barrier to contraceptive use in terms of fear of side effects by users.…”
Section: The Power Of Inclusive Sex Education and Contraceptionmentioning
confidence: 74%
“…The effect of education on attitudes towards contraceptive use have been established. 26 A study in Thailand 53 found that adolescent women who achieve well in school and do not exhibit risk behaviours are more likely to become pregnant when they do not have sufficient knowledge and skills to protect themselves from risky sexual behaviours, and that adolescent men did not understand how contraceptive methods worked.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have explored the experiences of pregnant adolescents and revealed that contraceptive decision-making is influenced by the quality and type of sexual health education, especially knowledge about contraception and adolescents’ perceptions regarding hormonal contraception as well as gender-based power imbalances in intimate relationships [ 29 31 ]. Gender roles and imbalances of power can influence the outcomes of adolescent sexual activity including pregnancy when girls lack the negotiation power to insist on contraception use [ 1 , 19 , 30 , 32 ]. The influence of gender roles on sexual and reproductive health may be presented in terms of existing gender power imbalance and the assumption that males have higher social status than females [ 30 , 33 ].…”
Section: Introductionmentioning
confidence: 99%